2014
DOI: 10.1002/pssa.201400043
|View full text |Cite
|
Sign up to set email alerts
|

FZ and CZ crystal growth: Cost driving factors and new perspectives

Abstract: In the field of monosilicon crystal growth, the Czochralski (CZ) as well as the floating zone (FZ) method have grown to a mature technology over the last 60 years and, until today, the costs have been continuously reduced. The cost driving factors for CZ and FZ are reviewed with respect to further potential improvements. Generally, the cost for the feedstock material is still dominanting the cost of ownership for both methods despite the dramtic decrease of the poly silicon price over the last years. This is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…LOAT-zone (FZ) silicon is considered to have high purity and little contamination [1]. For photovoltaic applications, FZ silicon wafers are often used for high efficiency solar cells [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…LOAT-zone (FZ) silicon is considered to have high purity and little contamination [1]. For photovoltaic applications, FZ silicon wafers are often used for high efficiency solar cells [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that hydrogenation improves the lifetime of minority carriers in Si crystals grown by the float-zone technique (FZ-Si) [10]. FZ Si is generally considered to be very good-quality material with high minority carrier lifetime, a low concentration of metals and relatively low oxygen content but at higher cost than Si grown by the Czochralski technique [11]. However, it has been found recently that in FZ-Si crystals a severe degradation of minority lifetime occurs upon thermal treatments in the temperature range between 450 • C and 800 • C, which is caused by the introduction of a sequence of electrically active defects with deep energy levels [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that these thermally-induced defects are associated with the presence of grown-in vacancies and vacancy complexes [13,15,16]. The degradation is more severe in crystals grown in a nitrogen ambient [15], which is widely used in recent years to suppress the formation of vacancy aggregates that can grow into extended defects such as voids [11]. These lifetime limiting defects can be permanently annihilated by high temperature treatments [14], during which the nitrogen effuses from the Si leaving a concentration undetectable (<5 × 10 13 cm −3 ) by secondary-ion mass spectroscopy (SIMS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Three samples (F1-F3) were cut from a zone melting ingot. [25] This process although costly allows producing mono-crystalline samples with a very low level of contamination (Sample type F in Table 1). Sample Cz was cut from a Czockralski ingot.…”
Section: Sample Originmentioning
confidence: 99%